A new genus of the Cupressaceae (sensu lato) from the Jurassic of Patagonia: Implications for conifer megasporangiate cone homologies - Escapa, Ignacio Hernán (2008)
A new conifer, Austrohamia minuta, gen. et sp. nov., from the Jurassic of Chubut province, Argentina, is described and proposed as the type species of a new genus of the Cupressaceae s.l. The material consists of impressions represented by well-preserved leafy twigs and branches as well as ovulate and pollen cones. The ovulate cones show a simple organization with helically arranged bracts, each bearing one or two inverted ovules on their adaxial surfaces. Pollen cones occur in terminal clusters subtended by modiﬁed leaves. This conifer possesses a combination of characters indicating placement within the basal Cupressaceae (i.e. the former “Taxodiaceae”). This conclusion is supported by a phylogenetic analysis that places the Argentinean fossil close to the extant genera Athrotaxis and Cunninghamia, and the fossil genera Elatides and Sewardio- dendron. In this context some classical characters in conifer systematics are reconsidered in order to clarify their homologies and signiﬁcance in the early evolution of the Cupressaceae. This represents the ﬁrst convincing record of the Cupressaceae s.l. in Jurassic oras from the southern hemisphere.